2013
DOI: 10.1159/000354565
|View full text |Cite
|
Sign up to set email alerts
|

Lausannevirus Seroprevalence among Asymptomatic Young Adults

Abstract: Objectives: The giant Lausannevirus was recently identified as a parasite of amoeba that replicates rapidly in these professional phagocytes. This study aimed at assessing Lausannevirus seroprevalence among asymptomatic young men in Switzerland and hopefully identifying possible sources of contact with this giant virus. Methods: The presence of anti-Lausannevirus antibodies was assessed in sera from 517 asymptomatic volunteers who filled a detailed questionnaire. The coreactivity between Lausannevirus and amoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 11 publications
(19 reference statements)
0
30
0
Order By: Relevance
“…Unexpectedly, seroprevalence studies conducted in the general population showed high (up to 13%) positivity rates of Marseillevirus IgG, which suggested a common human exposure ( 3 5 ). Presence of Marseillevirus in a symptomatic human was reported in 2013 in an 11-month-old boy with lymphadenitis and possibly corresponded to a primary infection ( 6 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, seroprevalence studies conducted in the general population showed high (up to 13%) positivity rates of Marseillevirus IgG, which suggested a common human exposure ( 3 5 ). Presence of Marseillevirus in a symptomatic human was reported in 2013 in an 11-month-old boy with lymphadenitis and possibly corresponded to a primary infection ( 6 ).…”
mentioning
confidence: 99%
“…Metagenomics then unexpectedly identified Marseillevirus-related sequences in blood of healthy donors ( 3 ), which was confirmed by PCR, fluorescence in situ hybridization, and serologic testing. Further PCR and serologic studies suggested substantial exposure of humans to marseilleviruses ( 4 , 5 ). …”
mentioning
confidence: 99%
“…Indeed, PCR-positive results must be confirmed using other primer sets (as was the case for primers ORF152 and ORF268 in the original blood donor study [2]), using other techniques (such as serology, microscopy, FISH, IF, immunohistochemistry, whole-genome sequencing, and proteomics, as in our previous studies [13]), and by other laboratories. Of note, independent of our work, Gilbert Greub's team in Lausanne detected Lausannevirus, another Marseillevirus, with a seroprevalence ranging from 1.74% to 2.51% in healthy Swiss men [4]. …”
mentioning
confidence: 99%
“…Also, for the first time, these techniques have enabled the isolation of Mimivirus from a respiratory sample [18,19] and the stools of a patient with pneumonia [20]. However, it is likely that serology is more effective in the detection of specific antibodies against the Marseilleviridae family, as related in Gilbert Greub's work in this journal [21]. …”
mentioning
confidence: 99%
“…Mimivirus seems to be linked to pneumonia and Marseillevirus is associated with asymptomatic carriage into blood [13] or in feces [22]. A case of adenitis in a young child has been identified [14] and antibodies to this virus have been found in blood donors [13,21]. …”
mentioning
confidence: 99%